PENGARUH DOSIS PUPUK KNO3 DAN PUPUK KANDANG TERHADAP PERTUMBUHAN TANAMAN TOMAT (Lycopersicum esculentum Mill.) VARIETAS BETAVILA YANG DIPANGKAS PUCUK APIKALNYA - Maria Klara Salli; Yosefina Lewar (Partner, 2019)
The study aims to determine the influence of KNO3 and manure to plant growth of the tomato varieties Betavila. Research takes place from April to November 2019 in Kupang District. This research uses randomized complete block design by one factor, which is 8 levels of fertilizer dose and repetition 4 times. As for the following treatment: P1 = 100% KNO3 recommendation, P2 = 100% Goat Manure recommendation, P3 = 100% KNO3 + 15 tons/ha goat manure, P4 = 100% KNO3 + 30 tons/ha goat manure, P5 = 75% KNO3 + 15 ton/ha goat manure, P6 = 75% KNO3 + 30 tons/ha goat manure, P7 = 50% KNO3 + 15 ton/ha goat manure, P8 = 50% KNO3 + 30 ton/ha goat manure.The results showed a combination of KNO3 and goat manure that affected the number of productive branches, buns and flower petals, and did not affect the lateral branches formed.  75% KNO3 + 30 tons/ha goat manure treatment provides the best influence on the number of productive branches (12.123), bunching of Flowers (27.973), and Flowers (5.630). Keywords: KNO3, goat manure, plant growth, tomato Betavila